The effect of addition of olive mill wastewater and phosphogypsum on some indicators of potato growth and production in the Mayar Shaker area in tartous governorate - كبيبو, عيسى; بوعيسى, عبد العزيز; زيدان, رياض; شاهين, حيدر (Latakia University Journal -Biological Sciences Series, 2021)
A study was conducted to study the effect of adding olive mill wastewater and phosphogypsum as a secondary product from phosphate fertilizer industry to some potato growth and productivity indicators during two consecutive seasons. spring loop, in the village of mayar shaker in tartous governorate. Potato growth indicators (plant height, leafy surface area, fresh and dry weight of shoots, and the number of the areal stems) were studied, as well as some of the total productivity indicators, the number of tubers, average weight of the marketing tubers and the total productivity. The results of the study showed for two consecutive seasons that the treatment added to olive mill wastewater and phosphogypsum exceeded the control and all other treatments, as the first came the traditionally fertilized treatment and olive mill wastewater and phosphogypsum followed by the traditional treatment with olive mill wastewater added. Additive olive mill wastewater treatments outperformed the additive factors of phosphogypsum, and this may due to richness and balance of olive mill wastewater with primary and secondary elements compared to phosphorous. Adding olive mill wastewater of 150 m3/ ha and 3% phosphogypsum compensated for about 80% of the amounts of mineral and organic fertilizers recommended for planting potatoes and thus material savings and environmental safety to dispose of two products from manufacturing products in a safe and beneficial manner. The improvement in the growth indicators was reflected in the increase in the total and marketing productivity in the potato crop, as the traditional treatment with olive mill wastewater and phosphogypsum gave a high production of 57463 kg/hectare, compared to 42071 kg/hectare for the fertilized treatment by the recommended method, with an increase of 211% compared to the control, as well as an increase in marketing production 94% compared to 73% with the control.